Massively parallel sequencing of Cannabis sativa chloroplast hotspots for forensic typing - Madeline G. Roman; Ryan Gutierrez; Rachel Houston (BMC, 2022)
Abstract Background Marijuana (Cannabis sativa) is the most commonly used illicit drug in the USA, and the use of DNA barcodes could assist drug trafficking investigations by indicating the biogeographical origin and crop type of a sample and providing a means for linking cases. Additionally, the legality of marijuana in the USA remains complicated with some states fully legalizing marijuana for recreational use while federally marijuana remains completely illegal. Massively parallel sequencing (MPS) offers distinct advantages over capillary electrophoresis (CE), including more comprehensive coverage of target loci, analysis of hundreds of markers simultaneously, and high throughput capabilities. Methods This study reports on the development of a MiSeq FGx® assay targeting seven "hotspot" regions in the Cannabis sativa chloroplast genome that are highly polymorphic and informative in attempts to determine biogeographical origin and distinguishing between marijuana and hemp. Sequencing results were compared to previous studies that used CE-based genotyping methods. Results A total of 49 polymorphisms were observed, 16 of which have not been previously reported. Additionally, sequence data revealed isoalleles at one locus, which were able to differentiate two samples that had the same haplotype using CE-based methods. This study reports preliminary results from sequencing 14 hemp and marijuana samples from different countries using the developed MPS assay. Conclusion Future studies should genotype a more comprehensive sample set from around the world to build a haplotype database, which could be used to provide investigative leads for law enforcement agencies investigating marijuana trafficking.